PEMENUHAN HAK KESEHATAN BAGI NARAPIDANA DI RUMAH TAHANAN NEGARA KELAS II B KEBUMEN - Dimas, Dimas Darmawan (Universitas Tadulako, 2021)
Prisoners are convicts who undergo the crime of missing independence in a penitentiary. Therefore, the Government through the Directorate General of Corrections must guarantee the fulfillment of their other rights, one of which is the right to obtain optimal health services both physically, mentally, spiritually and socially. This study aims to determine and explain the fulfillment of health rights for inmates in Kebumen State Class II B Detention Centers as well as any obstacles that arise in fulfilling the prisoners' health rights. This type of research is legal research with empirical juridical approach or sociological legal research. The data collection technique is done through field research and literature with qualitative data analysis techniques. Based on the results of the study, it is known that the fulfillment of prisoners' health rights is based on applicable laws and regulations such as providing health education and referring prisoners who are seriously ill to the hospital. Then the obstacles that arise in fulfilling prisoners' health rights are the limitations of health workers, the lack of health facilities and infrastructure, and the conditions of detention centers that are overcapsed. The solution is to improve the quality and ability of employees, as well as the addition of adequate health facilities and clinic space.